A Study on Purchase Behavior of Consumer Durable Goods with Special Reference to Tiruvarur District (International Journal of Scientific Research and Management (IJSRM), 2018)
The consumer durable goods industry is operating in a highly competitive, complex and rapidly changing business environment. Business leaders of consumer durable white goods organizations know their importance of having ready to access timely, accurate, consistent information and data for the purpose of establishing, nurturing and managing customer relationships across divisions. The research paper deals with the study on purchase behavior of consumer durable goods in Tiruvarur district.